A Green, One-Pot Synthesis of Substituted 2,3-Dihydroquinazoline-4(1H)-ones in the Presence of N-Sulfonic Acid Pyridinium Chloride - Azimi, Seyedeh Bahareh; Azizian, Javad (Synlett, 2016)
We present a one-pot method for the synthesis of 2,3-dihydroquinazoline-4(1H)-ones. The three-component reaction between isatoic anhydride, primary amines, and dialkyl acetylenedicarboxylates in the presence of N-sulfonic acid pyridinium chloride under solvent-free conditions affords the corresponding alkyl 2-[(alkoxycarbonyl)methyl]-1,2,3,4-tetrahydro-3-alkyl-4-oxo-quinazoline-2-carboxylates in excellent yields.
Keywords: three-component reaction; N-sulfonic acid pyridinium chloride; 2,3-dihydro-4(1H)-quinazolinones; solvent-free; green synthesis